DESIGN AND DEVELOPMENT OF ARCHIVE MANAGEMENT APPLICATION IN EAST JAVA LAMONGAN AREA OF SERVICE - Ra'uf, Dicky Pratama Putra; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Badan Kepegawaian Daerah is a government agency that has the task to make the formulation and implementation of policies and conduct education and training. Currently BKD has managed all employment documents. management is still done manually, the absence of recording of borrowing and return of documents. Problems - problems that arise from the condition of the company above is the loss of archival documents because the return is not returned properly due to lack of loan record. In addition, when searching documents will take a long time ranging from 30 to 60 minutes depending on the number of documents sought. It also happens to not get the document while searching, because when the document is completed lent is not returned properly or misplaced in the process of return. The next problem is the absence of recording while borrowing documents and also returning documents. The problem caused no history of the document whether it has been returned or has not been returned so that the impact when searching the document because there is no document information being borrowed or not.To solve the problem, the Archives Archive Management Dictionary will be created which can record all document management activities